Pengaruh LKS Berbasis Problem Solving untuk Meningkatkan Keterampilan Berpikir Kritis Siswa - Sari, Eka Novita; Rudibyani, Ratu Betta; Sofya, Emmawaty (FKIP Universitas Lampung, 2018)
The Effect of Problem Solving Based Worksheet to Improve Students Critical Thinking Skill. This research aims to describe the effect of using problem solving based worksheet to improve students critical thinking skills. The research design used is non equivalence pretest-posttest control group design. The sample of this research were students in class X MIPA 2 as control class and X MIPA 3 as experiment class, which were selected by cluster random sampling. The research data consisting of the values of pretest, posttest and n-Gain. The effect of worksheet to improve students critical thinking skill is calculated using the effect test formula. The results of data analysis and calculations show that worksheets applied to the experimental class have a greater effect than the control class. Therefor, it can be concluded that problem solving based worksheet has been taken effect to improve students critical thinking skills.Keyword: problem solving based student worksheet, critical thinking, electrolyte and non-elektrolyte solution. DOI: http://dx.doi.org/10.23960/jpmipa/v19i2.pp75-86